2021
DOI: 10.1186/s12913-021-06985-1
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of Iranian sixth five-year economic, social, and cultural development plan from universal health coverage perspective

Abstract: Background This research analyzed the Sixth Five-Year Economic, Social, and Cultural Development Plan of the Islamic Republic of Iran (6NPD) to shed light on how the plan addresses the Universal Health Coverage (UHC). Methods This research was a qualitative study. We systematically analyzed ‘Secs. 14 -Health, Insurance, Health & Women, and Family’ in the 6NPD. Through a content analysis, we converted this section into meaning units and coded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Even though it is emphasized in the Sixth Five-Year Development Plan that all foreigners living in Iran should be covered by health insurance [ 33 ], UIs still lack insurance coverage [ 34 ]. Therefore, they are forced to pay all costs OOP when receiving health care services, which can lead to significant financial hardships for them, and in many cases, they refuse to request needed services and follow their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is emphasized in the Sixth Five-Year Development Plan that all foreigners living in Iran should be covered by health insurance [ 33 ], UIs still lack insurance coverage [ 34 ]. Therefore, they are forced to pay all costs OOP when receiving health care services, which can lead to significant financial hardships for them, and in many cases, they refuse to request needed services and follow their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the health service at the point of care in 5YPFDs also did not persist. [ 73 74 75 ] This issue could be a sign of political unwillingness because it occasionally addresses the quality of the health service at the point of care depending on the prevailing opinion of experts. The results of a study showed that whenever senior management within the health system of Iran changes, different strategies are then established and followed.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the estimations can show how much the fuel prices should potentially change to manage the fossil fuel demand for achieving the UN targets (according to the price elasticities). Following this analysis, the effects of implementing the hypothetical price policy on the environment, economy and health are then estimated as a measure of sustainability (Mahdavi and Sajadi, 2021; Nasrollahi et al , 2020; Parsa et al , 2019). More details of the methodology are in the Appendix (Section A.1).…”
Section: Methodology and Datamentioning
confidence: 99%